Relative age effect and soccer refereeing: A `Strategic Adaptation` of relatively younger children? - Delorme, N.; Radel, R.; Raspaud, M. (European Journal of Sport Science, 2013)
Previous research suggested that the relative age effect (RAE) has a psychological influence on children and their decision to engage in a particular sport. Relatively younger children seem to have lower self-esteem. Indeed, because of the disadvantages of being younger, it is assumed that these players experience more situations of failure and inferiority. Because of these negative performance cues, it is likely that these young players feel less competent, which eventually leads to a higher dropout rate. These children can also decide to participate in sports in which physical attributes are less important. This shift from one sport to another can be interpreted as a `strategic adaptation`. The purpose of this study was thus to investigate whether refereeing could be another form of `strategic adaptation`. If a child chooses a specific sport but then does not feel competent enough to be a player, refereeing might be an alternate path followed to stay in the environment of a sport they like. Given the minimal age limits for refereeing, two hypotheses were formulated: (1) `reversed` RAE would be observed in district referees younger than 18 years old and (2) no RAE would be observed in district referees older than 18 years old, regional referees and national referees. The birthdates of all official male soccer referees (n=13,952) were collected from the federation database. Results show that the distribution of all district referees was significantly unbalanced (X2=18.73, df=3, P<0.001) with an over-representation of individuals who were born in the second half of the competitive year. As expected, this imbalance was exclusively located in district referees of 18 years old and less (X2=8.03, df=3, P<0.05), while the distribution was uniform for adults (X2=5.17, df=3, P<0.16). Concerning regional referees (X2=2.09, df=3, P<0.554) and national referees (X2=3.75, df=3, P<0.290), the results also provide support for our initial hypothesis as uniform distributions were found for both groups. This study brings to light new elements in the potential relationship between relative age and refereeing. Qualitative and/or longitudinal research is needed to confirm our quantitative data.